SOCIAL NETWORKS AS TOOLS TO ENRICH LEARNING ENVIRONMENTS IN HIGHER EDUCATION - González Pérez, Alicia (Bordón. Revista de Pedagogía, 2018)
INTRODUCTION. Digital technologies offer new educational opportunities in a connected society, where learning to work with others and self-regulated learning processes have become important elements that are enriched through interactions, improve learner engagement, and increase the sense of community. METHOD. The purpose of this case study was to analyse the perception of students, who use social networks as learning environments. To this end, reflective notes were gathered from students and analysed by Nvivo Pro Version 11. The final sample consisted of 15 students (cases), who successfully accomplished all the assignments. The students came from Nesna University College (Norway), the University of Szczecin (Poland) and the University of Extremadura (Spain). RESULTS. The results provide some clues about the students’ engagement in the process of creating knowledge through social networks considering the pedagogical, technological and social factors analysed. Norwegian and Polish students are more autonomous learners; they reflected more on the process through which they learnt with technology, and they self-regulated their learning process. In all three countries, most of them spent a lot of time learning how to use the social networks selected in the study and posting information. The students consider very important the role that connectivity and interaction play when they use any social network. DISCUSSION. Technology is a powerful tool for extending and creating opportunities to innovate in higher education, and social networks offer new ways for learning in an increasingly connected society, in which learning to work with others and collaborate has become extremely important skills to take into consideration. Promoting student-centred learning approaches to encourage and engage learners in decision-making and in the learning process is an effective strategy to exploit learning opportunities in online courses. Students value the importance of self-regulating their own learning to achieve goals, gain knowledge and acquire skills. Collaborative learning is key to empower students as the main protagonists of their own learning processes.